Bioactive polyacrylamide hydrogels with gradients in mechanical stiffness. Issue 5 (4th January 2013) - Diederich, Vincent E.G.; Studer, Peter; Kern, Anita; Lattuada, Marco; Storti, Giuseppe; Sharma, Ram I.; Snedeker, Jess G.; Morbidelli, Massimo
Abstract We propose a novel, single step method for the production of polyacrylamide hydrogels with a gradient in mechanical properties. In contrast to already existing techniques such as UV photo‐polymerization with photomasks (limited penetration depth) or microfluidic gradient mixers (complex microfluidic chip), this technique is not suffering such limitations. Young's modulus of the hydrogels was varied by changing the total monomer concentration of the hydrogel precursor solution. Using programmable syringe pumps, the total monomer concentration in the solution fed to the hydrogel mold was varied from 16 wt% down to 5 wt% over the feeding time to obtain a gradient in compliance ranging from 150 kPa down to 20 kPa over a length of 10 mm down to 2.5 mm. Polymerization was achieved with the dual initiation system composed of ammonium persulfate and N, N, N′, N′‐tetramethylethylenediamine, which were both fed through separate capillaries to avoid premature polymerization. Functionalized with the model ligand collagen I, the substrates were bioactive and supported the attachment of human foreskin fibroblasts (around 30% of the cells seeded attached after 1 h). A kinetic morphology study on homogeneous hydrogels of different stiffness's indicated that fibroblasts tend to spread to their final size within 2 h on stiff substrates, while the spreading time was much longer (ca. 4–5 h) on soft substrates. These trends were confirmed on hydrogels with compliance gradients, showing well spread fibroblasts on the stiff end of the hydrogel after 2 h, while the cells on the soft end still had small area and rounded morphology. Biotechnol. Bioeng. 2013; 110: 1508–1519. © 2012 Wiley Periodicals, Inc.